Taking badges to school: A school-based badge system and its impact on participating teachers. (April 2016) - Wardrip, Peter Samuelson; Abramovich, Samuel; Kim, Yoon Jeon; Bathgate, Meghan
Abstract: While current research on badges typically examines the relationship between badges and learners' motivation, this study explores a badge system's impact on participating teachers. Through qualitative analysis, the data suggests that the badge system provides teachers with new information about students not readily available through typical school-based interactions. Additionally, while the badge system initiated new meetings and opportunities for teachers' joint work, the data did not suggest that these collaborative activities established a public practice of instruction for participating teachers nor did the teachers report changes in their instructional practice. The paper ends with implications and plans for future research. Highlights: This study presents an empirical account of badges implemented in a school. Badges provided teachers with a means to new data about their students. The badge system initiated new meetings and chances for joint work among teachers. These collaborative activities did not establish a public practice of instruction. Most teachers did not perceive instructional changes related to badge involvement.